Adolescents with Epilepsy: Special Consideration for Teens with Epilepsy, Prevention of Injuries and Nurses Role - Mohan S; Bharathi M (RGUHS Journal of Nursing Sciences)
It is well recognized that young individuals with neurological impairments such as epilepsy receive less suitable assistance than young people with other chronic diseases. The period between the ages of 13 and 19 surrounding the transition to adult services is particularly crucial for promoting young peoples continued control and self-care. Epilepsy-specific biological psychosocial and biological variables can both hinder and facilitate the sharing of information and the development of self-care behaviors. The goals of the present review were to explain how young people with epilepsy aged 13 to 19 years and their parents experienced sharing information in healthcare settings to identify characteristics that affect both good and negative healthcare communication and identify what is known to be beneficial in doing so. Seizures which are frequent bursts of electrical activity in the brain are brought on by epilepsy. By the time they are adolescents almost two-thirds of all children with epilepsy outgrow their seizures. Epilepsy however maybe a lifelong condition for certain people. To better comprehend their childs condition and treatment parents should work together with their medical professionals.